Avaliação técnica e ambiental da reciclagem via oxidação química demembranas de osmose inversa descartadas - Eduardo Coutinho de Paula (2017)
The reverse osmosis (RO) technology for water desalination and demineralization serves the global water crisis context, both technically and economically, and its market is growing. However, the membrane modules have a limited life cycle between five and seven years. Theoverall objective of this study was to evaluate the technical and environmental feasibility of discarded RO membranes recycling by chemical oxidation process, for applications of recycled membranes in other separation processes with less rigorous specifications. Therecycling technique evaluated consisted in to cause the exposition of RO thin film composite membrane with oxidant solutions, in order to remove its dense layer of aromatic polyamide and subsequent conversion to the porous membrane. Procedures for membranes chemical cleaning were evaluated. Factors such as oxidant agents, concentration and pH of thesolutions, contact mode, operating pressure, and treatment time were evaluated in the oxidative treatment. The sodium hypochlorite (NaClO) and potassium permanganate (KMnO4) solutions exhibited great effectiveness to modify the selective properties of RO membranes, however the NaClO bath presented higher physical and chemical stability than the KMnO4 bath. In terms of water permeability, taking as a basis the pristine RO membrane (~3.0 L·h-1·m-2·bar-1, equivalent to 8.3·10-12 m3·s-1·m-2·Pa-1), membranes oxidized with NaClO (pH 11) had an increase of 27 to 39 times. Characterization techniques revealed notablechanges on the main physical-chemical properties of the recycled membranes, such as morphology, roughness and hydrophobicity. Tendency to fouling of recycled membranes was also evaluated. The permeate produced from the treatment of different surface waters usingthe recycled membrane complied with the Brazilian standards of potability, according to the Ordinance 2914/2011, for the following analyzed parameters: apparent color, turbidity, Escherichia coli, and heterotrophic bacteria. The pilot test using a recycled membrane modulefor water treatment performed similarly to that reported by several authors who evaluated commercial ultrafiltration (UF) spiral modules. Finally, based on the MIPS (Material input per service unit) eco-efficiency tool, the environmental benefits from direct and indirect recycling of the end-of-life RO membranes were estimated.